Pengaruh Efikasi Diri Dan Dukungan Sosial Terhadap Burnout Dalam Implementasi Kurikulum Merdeka Pada Guru Sekolah Dasar Negeri Di Kecamatan Sengah Temila - Werenfridus, Werenfridus; Mashudi, Mashudi; Zakso, Amrazi (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to; 1) analyze the effect of self-efficacy on burnout, 2) analyze the effect of social support on burnout, 3) analyze the effect of self-efficacy and social support simultaneously on burnout. This study uses a quantitative method with a causal associative design. The population of this study was 120 elementary school teachers in Sengah Temila District who had implemented the independent curriculum. The sample was taken using the total sampling technique so that the number of samples used was the same as the population. Based on interviews with first and fourth-grade teachers at SDN 09 Tampi Bide, SDN 53 Tampala'as, and SDN 57 Pakatan in Sengah Temila District who have implemented the Merdeka Curriculum, several challenges were found in the implementation of the Merdeka Curriculum at the school. Teachers still face difficulties in understanding the concepts and principles of the Merdeka Curriculum due to the lack of direct training related to the Merdeka Curriculum. The training that has been followed was conducted online, while internet networks are still limited. In addition, the lack of technology infrastructure is also an obstacle for teachers to access information related to the Merdeka Curriculum through the Merdeka Mengajar Platform (PMM), which can eventually cause boredom among teachers. The results of the study showed that; 1) self-efficacy had no significant effect on burnout, 2) social support had a negative and significant effect on burnout, and 3) self-efficacy and social support simultaneously had a significant effect on burnout. The contribution of both variables to burnout is 7.3%.